HIV/AIDS epidemic in a western border municipality of Rio Grande do Sul, Brazil: evolution, HIV cascade of care and lethality - Davoglio,Rosane Silvia (2021)
ABSTRACT: Objective: To analyze the characteristics and trends of HIV/AIDS epidemic in Uruguaiana, Rio Grande do Sul, between 2005 and 2015 through indicators related to infection and the cascade of care of people living with HIV/AIDS (PLWHA). Methods: Descriptive study performed with data from the Health Information Systems of the Ministry of Health. Historical sets of indicators related to detection of HIV/AIDS cases and deaths were developed, comparing with national and state data from 2005 to 2015. Also, the cascades of care for PLWHA were elaborated for the municipality between 2013 and 2015. Results: AIDS detection rates of Uruguaiana were higher in comparison to the country and state, the same happened with the mortality and lethality indicators, which varied between 35.1 and 17.7 deaths/100,000 inhabitants and 6.5 and 2.7 deaths/100 inhabitants, respectively. The cascades of care for PLWHA showed an increase in individuals diagnosed with HIV in the period (from 1,125 to 1,527). The main gap occurred between the “diagnosed” and “connected” categories, expanding over time (78, 48 and 43.4%, respectively). There was a low proportion of individuals in the “undetectable viral load” category in the three years, ranging from 32 to 22.9%. Conclusion: Indicators of detection, mortality, and lethality due to HIV/AIDS are high in Uruguaiana, with an increase in the number of people diagnosed with HIV and decrease in their link with health services, suggesting the need for advances in strategies to attract and link PLWHA to the health care network.